Structural, electrical, optical and thermal properties of nickel selenide - Chin, Pik Yee (2015)
Fundamental studies are very crucial to generate new knowledge. In this respect, bulk material is useful to understand the characteristic of the material. Nickel selenide (NiSe) has been chosen because of its impressive photovoltaic properties and a wide range of industrial applications. To improve the solar conversion to electric efficiency, NiSe synthesized via solid state reaction method was annealed in the temperature range of 423 to 823 K. The NiSe was in 1:1 stoichiometric form with single phase hexagonal crystal structure. FESEM micrographs showed the NiSe particle was in nanometer size. As the annealing temperature increased, the crystalline size increased from 52.7 nm to 142.8 nm while the dislocation density decreased from 36.01 x 1013 lines/m2 to 4.90 x 1013 lines/m2. The NiSe was a p-type semiconductor. As the NiSe annealed temperature increased, the electrical resistivity decreased from 0.0037 Ωcm to 0.00015 Ωcm. In addition, the Hall mobility increased from 1.21 cm2/Vs to 15.06 cm2/Vs. However, the sheet Hall coefficient and the sheet carrier density of the sample remained constant at 0.017 cm2/C and 3.19 x 1020 cm-2 respectively. This indicates that at higher anneal temperatures, crystallite size will increase causing the electrical resistivity to decrease. Optical analysis showed that the annealed NiSe has direct transition band gap energy in the range of 2.13 – 2.47 eV which is consistent with literature values. The decreased in the band gap of the sample with increasing annealing temperature can be interpreted as the increased in the crystallinity of the synthesized material. Photoacoustics analysis showed that as the annealed temperature increased, the surface recombination velocity decreased from 428.39 cm/s to 389.62 cm/s, while the thermal diffusivity, the diffusion coefficient and the band to band recombination lifetime of the NiSe increased from the 13.42 x 10-2 cm2/s to 20.81 x 10-2 cm2/s, from 4.56 cm2/s to 5.10 cm2/s,from 1.86 μs to 2.46 μs, respectively. This indicates that the diffused excess carrier through the NiSe surface has increased. The increasing of the surface recombination process is due to the increasing of homogeneity and crystallinity of the samples. In conclusion, increasing annealing temperature on NiSe has increased the crystallite size and decreased the dislocation density. The electrical resistivity and optical band gap also decreased, while the Hall mobility and thermal diffusivity increased. This work has shown that optimizing the annealing temperature is an important process to improve the quality of the bulk NiSe.